Advanced educational technologies on the basis of creative approaches in teaching mathematics - E.O.Sharipov; S.Yu.Shodiyev (International Journal on Integrated Education, 2021)
Today, a creative approach to mathematics education provides students with the skills to direct themselves to the profession, to solve problems in their professional activities. In order to become competitive in the technologically advanced labor market in the world, students need to have a thorough knowledge of mathematics. It is known that in mathematics there are more opportunities to develop creativity and creative thinking by solving problems. The use of advanced teaching technologies in mathematics lessons improves the quality of lessons. This article discusses the role of mathematics and its “Person-oriented learning” technology in teaching, mainly, traditional approach to problem solving and creative approaches to problem-solving and logical proof methods are presented.